Profitabilitas Saham Syariah Yang Di Pengaruhi Perputaran Modal Kerja (Sektor Industri, Sektor Perdagangan Jasa dan Investasi, Serta Sektor Pertambangan, di ISSI Tahun 2012-2017) - muhamad saifidin (Adzkiya : Jurnal Hukum dan Ekonomi Syariah, 2021)
This study wants to see the extent to which the turnover of working capital owned by a company can generate profits for the company in the Islamic stock sector, especially in the Industry, Service Trade and Investment sector, as well as the mining sector which is listed on ISSI 2012-2017. The method in this research is using panel data regression method. The results obtained from the data processing show that cash turvoner does not affect the profit shares of the three sectors. Receivable turvoners seem to affect the Mining Sector, and the Trade, Service and Investment Sector. But it has no effect on stock returns in the Industrial sector. Meanwhile, inventory turvoners can only affect Islamic stocks in the industrial sector